RANCANGAN KONSEP SISTEM KONTROL PLTS OFF-GRID BERBASIS SCADA PADA LABORATORIUM TEACHING FACTORY - Febryanti Miserycordia Dareda; Firginia Mikhalla Takalamingan; Hevania Aguilera Sofice Kojongian; Ventje Ferdy Aror; Julianus Gesuri Daud (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study proposes a conceptual design of a SCADA-based (Supervisory Control and Data Acquisition) control system for an off-grid Photovoltaic Power System (PLTS) intended for the teaching factory laboratory of Politeknik Negeri Manado. The system is designed to perform continuous monitoring and centralized control of PLTS operational parameters through four integrated functional layers, namely the sensor layer, the control layer, the communication layer, and the supervisory layer. The proposed architecture integrates an RS-485 power meter type 2121, a current transformer (CT), a Hywell PLC, and an HMI into a single coordinated platform. The PLTS subsystem to be controlled consists of a monocrystalline solar module with 18–22% efficiency, a PWM-based Solar Charge Controller (PWM-SCC), and a lithium-ion battery as the energy storage unit. The control system uses the Modbus RTU protocol over RS-485 to ensure stable communication among components, while the HMI provides a real-time visual interface for the operator. This design emphasizes a modular, educational, and industry-oriented framework structured in accordance with IEC 61724-1 (2017). The proposed laboratory is designed to strengthen students’ technical competencies in PLTS installation, SCADA operation, and system maintenance, as well as to support SDGs 4 (Quality Education) and SDGs 7 (Affordable and Clean Energy).